2022
DOI: 10.3390/diagnostics12071734
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Evaluation of Adenoid Hypertrophy in Children by Flexible Nasopharyngoscopy Examination (FNE), Proposed Schema of Frequency of Examination: Cohort Study

Abstract: Objectives: To demonstrate the effectiveness of endoscopic assessment of the pharyngeal tonsil in defining the size of the adenoid hypertrophy in endoscopic examination that would be equivalent to intraoperative assessment as a large adenoid, and to determine the lowest necessary frequency of tests to assess the variability of its size. Methods: The study is based on an analysis of two groups of children diagnosed and treated in a children’s ENT outpatient clinic and ENT department. In the first group, adenoid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 37 publications
0
8
1
1
Order By: Relevance
“…Tonsils are an integral part of the lymphatic system. Their main role is to recognize surrounding antigens, activate the local and general defense line, and neutralize and destroy antigens as a result of the development of cellular and humoral responses (28).…”
Section: Dyskusjamentioning
confidence: 99%
See 1 more Smart Citation
“…Tonsils are an integral part of the lymphatic system. Their main role is to recognize surrounding antigens, activate the local and general defense line, and neutralize and destroy antigens as a result of the development of cellular and humoral responses (28).…”
Section: Dyskusjamentioning
confidence: 99%
“…B oraz tkanki międzygrudkowej, w której dominują grasiczozależne limfocyty T. Migdałki stanowią integralną część układu chłonnego. Główną ich rolą jest rozpoznawanie otaczających antygenów, uruchamianie miejscowej i ogólnej linii obrony oraz neutralizacja i niszczenie antygenów w wyniku rozwoju odpowiedzi komórkowej i humoralnej (28).…”
Section: Dyskusjaunclassified
“…Early diagnosis is therefore necessary to control symptoms and enhance treatment modalities. Zwierz et al grouped the various diagnostic methods into two categories: namely, invasive and imaging [54]. They further grouped techniques such as rigid or flexible fibreoptic nasopharynx endoscopy (FFNE), video fluoroscopy, acoustic rhinomanometry, physical examination by the finger or a mirror through the mouth as invasive.…”
Section: Techniques For Diagnosis 61 Adenoid Hypertrophymentioning
confidence: 99%
“…These procedures come with high costs, the need for ENT specialists and cutting-edge expensive equipments. Though Zwierz et al [54] reported that FFNE is invasive, Baldassari and Choi [109] highlighted that FFNE is minimally invasive and reliable among the paediatric population due to its effective and dynamic approach. Several other studies have also reported that FFNE is the gold standard for examining the nasopharynx which is less expensive as compared to the image techniques [50,[110][111][112][113][114][115][116].…”
Section: Techniques For Diagnosis 61 Adenoid Hypertrophymentioning
confidence: 99%
“…Yamada showed that an overgrowth of adenoids occurred in preschool children, but there were no significant changes in the adenoid size from 8–12 years of age [ 7 ]. A previous study based on flexible endoscopic examinations revealed that adenoid involution proceeds rather slowly; only 7.9% of preschool children (aged 3–7 years) underwent a change in the adenoid size by >15% on the adenoid to choana (A/C) ratio over one year of observation, 21.6% over a period of 2 years, and 45% over a period of 3 years [ 8 ]. The growth and development patterns of the nasopharyngeal lymphoid tissues vary for each individual; accordingly, we believe that in studies comparing the adenoid size in a pair of siblings, the permissible age difference should not exceed 12 months.…”
Section: Introductionmentioning
confidence: 99%